2017
DOI: 10.1158/1535-7163.mct-17-0309
|View full text |Cite
|
Sign up to set email alerts
|

The Irreversible Covalent Fibroblast Growth Factor Receptor Inhibitor PRN1371 Exhibits Sustained Inhibition of FGFR after Drug Clearance

Abstract: An increasing number of cancers are known to harbor mutations, translocations, or amplifications in the fibroblast growth factor receptor (FGFR) family of kinases. The FGFR inhibitors evaluated in clinical trials to date have shown promise at treating these cancers. Here, we describe PRN1371, an irreversible covalent inhibitor of FGFR1-4 targeting a cysteine within the kinase active site. PRN1371 demonstrated strong FGFR potency and excellent kinome-wide selectivity in a number of biochemical and cellular assa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 19 publications
1
23
0
Order By: Relevance
“…Together, these results suggested that the risk of drug resistance with futibatinib was low and infigratinib, which showed strong inhibition of FGFR1-3, but only marginal inhibition of FGFR4 in earlier studies (36,38,39). Similarly, PRN1371 has been reported to exhibit a 50-fold lower affinity for FGFR4 than for FGFR1-3 (26). Because futibatinib is a covalent inhibitor, it was expected that its inhibitory activity would persist even after short periods of exposure in the cells, as has been observed with other covalent inhibitors (26,41).…”
Section: Futibatinib Was Associated With a Low Risk Of Drug Resistancmentioning
confidence: 63%
See 4 more Smart Citations
“…Together, these results suggested that the risk of drug resistance with futibatinib was low and infigratinib, which showed strong inhibition of FGFR1-3, but only marginal inhibition of FGFR4 in earlier studies (36,38,39). Similarly, PRN1371 has been reported to exhibit a 50-fold lower affinity for FGFR4 than for FGFR1-3 (26). Because futibatinib is a covalent inhibitor, it was expected that its inhibitory activity would persist even after short periods of exposure in the cells, as has been observed with other covalent inhibitors (26,41).…”
Section: Futibatinib Was Associated With a Low Risk Of Drug Resistancmentioning
confidence: 63%
“…Similarly, PRN1371 has been reported to exhibit a 50-fold lower affinity for FGFR4 than for FGFR1-3 (26). Because futibatinib is a covalent inhibitor, it was expected that its inhibitory activity would persist even after short periods of exposure in the cells, as has been observed with other covalent inhibitors (26,41). However, as FGFR turnover was determined to be rapid (half-life ~4 hours) in the cell lines used in our study, the duration of futibatinib inhibition could not be accurately estimated.…”
Section: Futibatinib Was Associated With a Low Risk Of Drug Resistancmentioning
confidence: 99%
See 3 more Smart Citations